2006
DOI: 10.1111/j.1365-2141.2006.06019.x
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming graft rejection in heavily transfused and allo‐immunised patients with bone marrow failure syndromes using fludarabine‐based haematopoietic cell transplantation

Abstract: Summary Allogeneic haematopoietic cell transplantation (HCT) can cure a variety of non‐malignant haematological disorders. Although transplant outcomes for selected patients with severe aplastic anaemia (SAA) and paroxysmal nocturnal haemoglobinuria (PNH) have improved, older age, allo‐immunisation from transfusions, prior immunosuppressive therapy and a prolonged time from diagnosis to transplantation are associated with worse outcome. Because of its potent immunosuppressive effects, we investigated a fludara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
90
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 52 publications
3
90
1
1
Order By: Relevance
“…11,14 These studies demonstrate that a similar approach may be successful to cure the disease and interestingly suggest that an important "graft-versus-PNH" effect with reduced intensity conditioning transplant could be hypothesized. 19 The use of hematopoietic stem cell transplantation to treat paroxysmal nocturnal hemoglobinuria has become less frequent now that there is an effective drug therapy such as eculizumab.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…11,14 These studies demonstrate that a similar approach may be successful to cure the disease and interestingly suggest that an important "graft-versus-PNH" effect with reduced intensity conditioning transplant could be hypothesized. 19 The use of hematopoietic stem cell transplantation to treat paroxysmal nocturnal hemoglobinuria has become less frequent now that there is an effective drug therapy such as eculizumab.…”
mentioning
confidence: 99%
“…Thus, reduced intensity conditioning regimen should be restricted to prospective clinical trials; perhaps some specific reduced intensity conditioning regimens which seem to be as effective as myeloablative conditioning in a single center experience. 14 In conclusion, our survey shows that hematopoietic stem cell transplantation may lead to a long-term cure rate as high as 60% in a heterogeneous cohort of seriously ill paroxysmal nocturnal hemoglobinuria patients but improvements in hematopoietic stem cell transplantation procedure are still desirable. While the recent availability of targeted therapy has certainly reduced the indication for hematopoietic stem cell transplantation, its potentially curative use remains a valid therapeutic option for patients candidate to a low-risk transplant procedure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Graft failure and graft rejection are known to be high in patients with non-malignant diseases. 6,7 This may be because of the fact that there has been no earlier chemotherapy to the risk of immunization from repeated transfusions in hemoglobinopathies, and to the use of less myeloablative-conditioning regimens. In recent years, an increasing number of patients with non-malignant diseases have been treated with reduced intensity conditioning (RIC) to reduce acute toxicity and late side effects.…”
Section: Introductionmentioning
confidence: 99%
“…8 In patients with SAA specifically, several noncomparative studies have reported encouraging results in the setting of HLA-matched related HSCT. [9][10][11][12][13] A recent report from the EBMT SAA working party retrospectively analyzed 30 patients older than 30 years receiving reduced-intensity conditioning HSCT (using fludarabine 30 mg/m 2 Â 4, CY 300 mg/m 2 Â 4 and most with ATG, namely a FCA regimen) and compared their outcome with a control group receiving the standard regimen (CY þ / À ATG) over the same study period (1998-2007). 14 Recipients of fludarabine-based conditioning had a higher probability of ageadjusted overall survival than the control group (P ¼ 0.04).…”
Section: Impact Of Conditioning Regimen Modifications In Older Patientsmentioning
confidence: 99%